RETRACTED: Tingkat Pemberian ASI dalam Orientasi Islam terhadap Kognitif Anak Usia 4–6 Tahun di Kota Malang - Dessy Putri Wahyuningtyas; Rikza Azharona Susanti (Aṭfāluna: Journal of Islamic Early Childhood Education, 2019)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Atfaluna: Journal of Islamic Early Childhood Education entitled “Tingkat Pemberian ASI dalam Orientasi Islam terhadap Kognitif Anak Usia 4–6 Tahun di Kota Malang”, Vol. 2, No. 1, pp. 1-12, June 2019 DOI: https://doi.org/10.32505/atfaluna.v2i1.862 This paper has been found to be in violation of Atfaluna: Journal of Islamic Early Childhood Education principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Jurnal Warna Vol. 3, No. 1, June 2019, pp. 60-75. The document and its content has been removed from Atfaluna: Journal of Islamic Early Childhood Education entitled and reasonable effort should be made to remove all references to this article.